Clinical Characteristics of Paediatric Pancreatitis Caused by Pancreaticobiliary Malformation: A Single-Centre Retrospective Analysis - Guo, Jing; Jia, Qian-ru; Sun, Mei (Frontiers in Pediatrics, 2021)
Abstract Background/Aims: To investigate the clinical profiles of children with pancreatitis caused by pancreaticobiliary malformation. Methods: We retrospectively analysed the clinical data of children diagnosed with pancreatitis at our institute from June 2017 to January 2021. Results: A total of 195 patients and 169 control subjects were included in this study. Twenty-six (13.3%) patients had pancreaticobiliary malformation-related pancreatitis. The average age of onset in the pancreaticobiliary malformation pancreatitis (PMP) group was lower than that in the non-PMP group, and the difference was statistically significant. The number of patients in the PMP group that had jaundice was significantly higher than that of the non-PMP group (P<0.05). Logistic regression analysis showed that total bilirubin (TB) and γ-glutamyltransferase (GGT) (odds ratio=1.096, P<0.01) were independent predictors of pancreaticobiliary malformation-related pancreatitis in children. The positive detection rate of pancreaticobiliary malformation was 68% for abdominal ultrasound, 38.4% for abdominal enhanced computed tomography, and 91.3% for magnetic resonance cholangiopancreatography (MRCP). The recurrence rate (34.6%) in the PMP group was higher than that in the non-PMP group (15.4%, P<0.05); surgical therapy had the lowest recurrence rate. Age at initial onset of pancreatitis was younger and the period to recurrence was shorter in the PMP group than in the non-PMP group (P<0.05). Conclusion: Pancreaticobiliary malformation is one of the major causes of paediatric pancreatitis. Elevated TB and GGT in patients with pancreatitis may be suggestive for underlying pancreaticobiliary malformation not solely to pancreatitis. MRCP should be used when pancreatitis due to pancreaticobiliary malformation is suspected. Surgery or endoscopic retrograde cholangiopancreatography-guided intervention may be helpful but further study is needed.